IMPACT OF BULLYING ON ACADEMIC PERFORMANCE OF SENIOR SECONDARY SCHOOL SCIENCE STUDENTS IN NORTH CENTRAL, NIGERIA - A.E.B, Ubom; I.A, Ojelade; S.O, Olamoyegun (Antis Publisher, 2025)
Objective: This study investigates the impact of bullying on the academic performance of senior secondary school science students in North Central, Nigeria. It examines the differences in academic achievement between bullied and unbullied students and explores gender disparities in bullying experiences. Method: A descriptive survey design was employed, with a sample of 384 students and teachers selected from government co-educational senior secondary schools in Niger State and the Federal Capital Territory using Krejcie and Morgan’s table. A purposive sampling technique was utilized, and data were collected through validated questionnaires. Instrument reliability was assessed using the test-retest method and Cronbach’s alpha coefficient (0.814). Data analysis was conducted using Mann-Whitney and T-tests via SPSS Version 21. Results: Findings revealed that unbullied students significantly outperformed bullied students academically. Males were identified as the predominant perpetrators, while females were the primary victims. The study also highlights effective anti-bullying strategies, including policy implementation, school climate improvement, teacher training, and student-led initiatives. Novelty: This study provides empirical evidence on the academic consequences of bullying within science education in Nigeria, emphasizing the need for targeted interventions. It contributes to the literature by proposing practical measures for school administrators and policymakers to mitigate bullying and support affected students.